Ekstrakurikuler Sebagai Dasar Pembinaan Olahraga Pelajar - Rasyono (Universitas Negeri Semarang, 2016)
Extracurricular is a place for students to channel their interests and talents beyond academic subjects in school. A wide variety of extracurricular activities among other fields of art, spirituality, leadership, journalism and no less popular and almost every school there are extracurricular sport. Enthusiastic and sports enthusiasts ekstrakuler school is remarkable. This condition is supported by the many competitions and championships between schools in the field of sports and even to the level of the multi event POPDA, O2SN, Popnas, even the base PPLP Championship athletes are students at school. Potential arising from this competitive climate makes the existence of extracurricular school as the granary of student athletes being very central and must be properly managed, focused and sustainable as basic sports coaching students.